Congenital Zika Syndrome: Prevalence of low birth weight and associated factors. Bahia, 2015–2017. (May 2019) - Carvalho-Sauer, Rita; Costa, Maria da Conceição Nascimento; Barreto, Florisneide R.; Teixeira, Maria Gloria
Highlights: Low Birth Weight in children with CZS is 4 times higher than in those without CZS. The prevalence of Low Birth Weight among children with CZS is very high, regardless of the duration of gestation. Prematurity and caesarean birth are associated with Low Birth Weight in CSZ children. Most of the children with CZS have mother of brown color, single and of low schooling. Abstract: Objective: The clinical manifestations of Congenital Zika Syndrome (CZS) are not fully known, for example its effect on birth weight. This study estimated the prevalence of low birth weight (LBW) among children with CZS, and identified associated factors. Methods: Cross-sectional study involving 393 children with CZS living in Bahia, Brazil, in 2015–2017. Official Information Systems were the data sources. We calculated LBW prevalence and applied Logistic Regression to assess associated factors. Results: Prevalence of LBW among children with CZS was 37.2%. Excluding pre-term births the proportion was 29.9%. This prevalence was 81.0% and 28.0% among children born pre-term and term/post term, respectively. There was a higher proportion (53.2%) in female children, and in those delivered by cesarean section (51.4%). Most mothers were single/separated (62.1%) and had a low level of schooling (70.0%). In the model adjusted for type of delivery, preterm births presented a 10.8 times greater chance of presenting LBW than term/post-term ones. However, the Confidence Interval was very wide. Adjusting for gestation duration, children born by cesarean section had a 1.63 higher probability of presenting LBW than those born by vaginal delivery (OR = 1, 63; CI95% 1.01, 2.63). Conclusions: The prevalence of LBW among children with CZS was very elevated, both preterm and term/post-term live births. This can contribute to increasing their risk for morbimortality. The association of LBW with prematurity and cesarean deliveries is known, but in children with CZS, it has not been clarified whether or not this is related to pathological conditions caused by fetal infection by the Zika virus.